Sosialisasi Penyakit Skabies dan Edukasi Pembuatan Sabun Organik di Pondok Pesantren Nurul Qur’an di Desa Mertak Tombok - Lalu Jupriadi; Dodiy Firmansyah; Dita Retno Pratiwi; Dedent Eka Bimaharyanto; Agung Suryawan; Dwi Ilham Abdika Putra; Putri Salindah Lestari; Winda Fitria; Azwar Hadi; Nurhasanah Nurhasanah; Weni Ari Wijayanti (Jurnal Abdimas Kesehatan (JAK), 2022)
Bath soap is a compound of sodium or potassium with fatty acids from vegetable oils and or animal fats in solid, soft or liquid form, used as a cleanser. The Nurul Qur'an Islamic boarding school is located in Mertak Tombok Village, Praya District, Central Lombok Regency, West Nusa Tenggara Province. The purpose of educational activities about scabies disease and training in making organic solid soap for the students and students of the Nurul Qur'an Islamic Boarding School was carried out to prevent and treat scabies disease. The method used is the distribution of questionnaires after socialization and education are carried out to students and female students. the activity showed that the students were very enthusiastic about the socialization of scabies disease and counseling on the manufacture of organic solid soap. The activity lasted for one month, namely in June 2022. The results of community service were obtained by increasing the ability of the students in soap making and understanding of the scabies disease.